Kearifan lokal Sebagai Upaya Pelestarian Taman Nasional Kerinci Seblat (TNKS) di Kabupaten Kerinci - Rintia, Rintia; Firza, Firza (DAS Institute, 2025)
Forest destruction will have a major impact on accelerating climate change. The groups most vulnerable to environmental impacts are indigenous communities, who grow and live by relying on forest products. As a country that is implementing the Sustainable Development Goals (SDGs) concept, forest degradation is a crucial problem, especially in part 15 of the SDGs goals, namely protecting land ecosystems. The parties responsible for this issue are of course every level of society which should strive to preserve nature and become conservation agents. Therefore, there is a need for further discussion regarding the application of local culture in preserving the Kerinci Seblat Park in Kerinci Regency. This research was conducted using qualitative methods relying on primary and secondary data. With data collection techniques such as observation, interviews and document analysis. The research results show that the preservation of the Kerinci Seblat National Park Forest (TNKS) is triggered by local wisdom regarding the myth of prohibiting disturbing the forest which is believed by the local community. People living in mountain forests are an ethnic minority group, possessing a wealth of local knowledge and skills in forest management. By maintaining forests through the help of local wisdom, this helps realize the 15th SDGs goal, namely the balance of terrestrial ecosystems.